Anesthetic induction with guaifenesin and propofol in adult horses - Brosnan, Robert J.; Steffey, Eugene P.; Escobar, André [UNESP]; Palazoglu, Mine; Fiehn, Oliver (Amer Veterinary Medical Assoc, 2011)
Objective-To evaluate whether guaifenesin can prevent adverse anesthetic induction events caused by propofol and whether a guaifenesin-propofol induction combination has brief cardiovascular effects commensurate with rapid drug washout.Animals-8 healthy adult horses.Procedures-Guaifenesin was administered IV for 3 minutes followed by IV injection of a bolus of propofol (2 mg/kg). Additional propofol was administered if purposeful movement was detected. Anesthesia was maintained for 2 hours with isoflurane or sevoflurane at 1.2 times the minimum alveolar concentration with controlled normocapnic ventilation. Normotension was maintained via a dobutamine infusion. Plasma concentrations of propofol and guaifenesin were measured every 30 minutes.Results-Mean +/- SD guaifenesin and propofol doses inducing anesthesia in half of the horses were 73 +/- 18 mg/kg and 2.2 +/- 0.3 mg/kg, respectively. No adverse anesthetic induction events were observed. By 70 minutes, there was no significant temporal change in the dobutamine infusion rate required to maintain normotension for horses anesthetized with isoflurane or sevoflurane. Mean plasma guaifenesin concentrations were 122 +/- 30 mu M, 101 +/- 34 mu M, 93 +/- 28 mu M, and 80 +/- 24 mu M at 30, 60, 90, and 120 minutes after anesthetic induction, respectively. All plasma propofol concentrations were below the limit of quantitation.Conclusions and Clinical Relevance-Guaifenesin prevented adverse anesthetic induction events caused by propofol. Guaifenesin (90 mg/kg) followed by propofol (3 mg/kg) should be sufficient to immobilize >99% of calm healthy adult horses. Anesthetic drug washout was rapid, and there was no change in inotrope requirements after anesthesia for 70 minutes. (Am J Vet Res 201172:1569-1575)